LncRNA FAM30A Predicts Adverse Prognosis and Regulates Cellular Processes in Colorectal Cancer via Modulating miR-21-3p - Ye, Guoxiang; Chen, Yanxiang (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Colorectal cancer (CRC) is a prevalent gastrointestinal cancer with high incidence and mortality rate. lncRNAs could regulate the expression of miRNAs and further affect cancer development. Previous research has suggested that FAM30A is involved in various cancer. We aimed to investigate the function of FAM30A in the prognosis of CRC and its underlying molecular mechanisms. Materials and Methods: Matched tissues were collected from 107 CRC patients. FAM30A was measured by quantitative real-time transcription polymerase chain reaction and its clinical significance was evaluated by its correlation with patients’ prognosis and clinicopathological features. Furthermore, the dual luciferase reporter assays were employed to assess the interactions between FAM30A and miR-21-3p and to evaluate the role of miR-21-3p in regulating the tumor suppressor effects of FAM30A. Cell proliferation and metastasis were evaluated by the Transwell assay and cell counting kit-8 assay. Results: FAM30A level was markedly decreased in CRC tissues (P < .001). A prominent association was observed in FAM30A with tumor– node–metastasis stage (P = .022), carcinoembryonic antigen (P = .027), and differentiation (P = .043) of CRC patients. The lower the FAM30A level was associated with the lower the survival rate of the CRC patients (log rank P = .034). FAM30A could negatively modulate miR-21-3p (P < .001), and the overexpression of FAM30A significantly suppressed CRC cell proliferation and metastasis (P < .001). The suppressive function of FAM30A overexpression was mediated by miR-21-3p. Conclusion: FAM30A can be considered a poor prognostic indicator in CRC. Decreased FAM30A can promote the proliferation and metastasis of CRC cells by negatively regulating miR-21-3p. Cite this article as: Ye G, Chen Y. LncRNA FAM30A predicts adverse prognosis and regulates cellular processes in colorectal cancer via modulating miR-21-3p. Turk J Gastroenterol. 2024;35(7):532-538.